The value of Furazolidone nf-180 and Terramycin antibiotic in the rations of fattening pigs in the dry lot. - Aubel, C.E. (Kansas Agricultural Experiment Station, 2011)
One of the most critical problems of the swine industry is disease. Antibiotics have been demonstrated to be effective in keeping some diseases at a low level. The nitrofurans have shown good results for certain specific diseases in poultry. Their effect in swine feeding is little known, for few experiments have been carried on feeding them to swine. This experiment was initiated to study the effect of furazolidone nf-180 in rations for growing and fattening swine. In this test four lots of fall pigs were self-fed free choice a basal ration of shelled corn and a mixed protein supplement in dry lot in winter. The mixed protein supplement was made up of 4 parts tankage, 4 parts soybean meal, 1 part linseed meal, and 1 part alfalfa meal.
Keywords: Swine; Terramycin; Protein